Oral Health Knowledge of Pregnant Women: A crosssectional study - Ihab Ahmed Rzaij; Diaa F. Jrood; Doaa Sami Rashash (Zien Journals, 2022)
Poor oral health during pregnancy has been linked to negative results for both the mother and the child, suggesting that it should be a priority in prenatal care. Hormonal alterations during pregnancy, and notable alterations in estrogen, have been linked to an increase in gum disease symptoms such as hyperemia, inflammation, bleeding, hypersensitivity of the gingiva, and risk of bacterial infection. The purpose of the study is to evaluate women's awareness of oral health during pregnancy and the correlation between women's knowledge and their socio-demographic attributes
Keywords: evaluate; Hormonal; demographic; oral health during